Data analysis using SQL and Excel - Linoff, Gordon (Wiley Pub., 2008)
"Data mining expert Gordon Linoff focuses on these topics and shows you how SQL and Excel can be used to extract business information from relational databases. He begins by taking a look at how data is central to the task of understanding customers, products, and markets, and he then goes on to show you how to use that data to define business dimensions, store transactions about customers, and summarize important data to produce results." "Each chapter explains when and why to perform a particular type of business analysis in order to obtain useful results, how to design and perform the analysis using SQL and Excel, and what you can expect the results to look like." "Throughout the book, critical features of Excel are highlighted, interesting uses of Excel graphics are explained, and dataflows and graphical representations of data processing are used to illustrate how SQL works."--Jacket
Title from title screen. - Includes index
Keywords: Microsoft Excel (Computer file); SQL (Computer program language); Querying (Computer science); Data mining; Data Mining; Microsoft Excel (Fichier d'ordinateur); SQL (Langage de programmation); Interrogation (Informatique); Exploration de données (Informatique); Bases de données; Interrogation; online searching; COMPUTERS; Data Processing; Dataprocessing; Microsoft Excel; SQL; Datamining